FRI0375 Delayed lupus nephritis in the course of systemic lupus erythematosus predicts a poorer renal response to induction therapy, renal flares, and worse long-term renal outcomes: a multicenter, retrospective cohort study. (12th June 2018) - Nakano, M.; Kubo, K.; Shirota, Y.; Iwasaki, Y.; Tanaka, N.; Takahashi, Y.; Tateishi, S.; Yamashita, H.; Miyazaki, M.; Sato, H.; Igari, T.; Kanda, H.; et al.
Abstract : Background: Some prognostic factors for lupus nephritis (LN) have been mentioned such as nephrotic syndrome, class 4 and chronicity on histology. In a previous single-centre study, we reported a potentially poorer renal response to induction therapy in LN that developed later after SLE onset (delayed, D-LN) compared with LN manifesting at SLE onset (early, E-LN) 1) . However, our study was limited by a small sample size and lack of long-term observation. Objectives: This multicenter study aimed to validate whether D-LN was a useful predictor of a poor response to induction therapy with more detailed clinical and pathological parameters. Furthermore, we investigated whether D-LN was also a predictor of flares and long-term renal outcomes in addition to the established prognostic factors. Methods: We retrospectively examined 215 biopsy-proven LN patients (136 E-LN, 79 D-LN) who attended 3 hospitals above between 1997 and 2014 and who were observed for 3–20 (median: 10.8) years from LN onset. We compared baseline clinical, pathological features and treatment options at LN onset between E-LN and D-LN. Then we compared the cumulative complete response (CR) rates, renal/extra-renal relapse rates, and the rates of renal insufficiency between the two groups. Renal insufficiency was defined as follows: 1 serum creatinine (SCr) doubling or ESRD for severe insufficiency, and 2 SCr increasing by 1.5 times and also >1.0 (female) or >1.2 mg/dl (male) for mild insufficiency. Moreover, we evaluated predictors of the response, flares and long-term renal outcomes with multivariate analysis. Results: Anti-Sm/RNP antibodies and mixed proliferative and membranous nephritis (class 3+5 or 4+5) were significantly more prevalent in D-LN than E-LN (48.1 vs. 32.4%, 68.8 vs. 40.4%, 40.5 vs. 18.4%, respectively). Log-rank test showed that significantly lower cumulative CR rates over 3 years (65.8 vs. 83.1% at 12 months, 83.5 vs. 92.6% at 36 months, p <0.01 ) and significantly higher relapse rates (both renal and extra-renal) over 20 years in D-LN than E-LN. Mild renal insufficiency was significantly more likely to occur in D-LN over 20 years (21.5 vs. 12.5%, p =0.04 ). We performed multivariate Cox regression analysis for the response, flare, and renal outcomes including significant variables on univariate analysis. As independent predictors of CR, D-LN, nephrotic syndrome and chronicity index were identified. As those of renal flares, D-LN was detected. Although D-LN was not associated with severe renal insufficiency, D-LN was identified as an independent predictor of mild renal insufficiency as well as some other factors (table 1). Conclusions: D-LN might be a novel predictor of a poorer treatment response, renal flares and long-term renal outcomes independent of the established prognostic factors. The distinct differences in the autoantibody profiles between E-LN and D-LN groups suggest that D-LN patients might reflect a refractory SLE subset with a specific immunological profile. Reference: [1] Nakano M, et al. Different responses to induction therapy in two onset categories of lupus nephritis.EULAR2017THU 0251. Acknowledgements: None Disclosure of Interest: None declared